Effects of MS-153 on chronic ethanol consumption and GLT1 modulation of glutamate levels in male alcohol-preferring rats - Alhaddad, Hasan; Kim, Nathaniel T.; Aal-Aaboda, Munaf; Althobaiti, Yusuf S.; Leighton, James; Boddu, Sai H. S.; Wei, Yangjie; Sari, Youssef (Frontiers in Behavioral Neuroscience, 2014)
We have recently shown that upregulation of glutamate transporter 1 (GLT1) in the brain is associated in part with reduction in ethanol intake in alcohol-preferring (P) male rats. In this study, we investigated the effects of a synthetic compound, (R)-(−)-5-methyl-1-nicotinoyl-2-pyrazoline (MS-153), known to activate GLT1 on ethanol consumption as well as GLT1 expression and certain signaling pathways in P rats. P rats were given 24-hour concurrent access to 15% and 30% ethanol, water and food for five weeks. On week 6, P rats received MS-153 at a dose of 50 mg/kg (i.p.) or a vehicle (i.p.) for five consecutive days. We also tested the effect of MS-153 on daily sucrose (10%) intake. Our studies revealed a significant decrease in ethanol intake at the dose of 50 mg/kg MS-153 from Day 1 through Day 14. In addition, MS-153 at dose of 50 mg/kg did not induce any significant effect on sucrose intake. Importantly, we found that MS-153 upregulated the GLT1 level in the nucleus accumbens (NAc) but not in the prefrontal cortex (PFC). In accordance, we found upregulation of nuclear NFkB-65 level in NAc in MS-153-treated group, however, IkB was downregulated in MS-153-treated group in NAc. We did not find any changes in NFkB-65 and IkB levels in PFC. Interestingly, we revealed that p-Akt was downregulated in ethanol vehicle treated groups in the NAc; this downregulation was reversed by MS-153 treatment. We did not observe any significant differences in glutamate aspartate transporter (GLAST) expression among all groups. These findings reveal MS-153 as a GLT1 modulator that may have potential as a therapeutic drug for the treatment of alcohol dependence.